The Turkish Traslation of Second Revised Draft of Legally Binding Instrument to Regulate, in International Human Rights Law, the Activities of Transnational Corporations and Other Business Enterprises and A General Comment Regarding Draft - Betül Karagedik (Public and Private International Law Bulletin)
.